Object oriented modeling: Retrospective systems information model for constructability assessment - Love, Peter; Zhou, Jingyang; Matthews, Jane; Lou, H. (Elsevier BV, 2016)
© 2016 Elsevier B.V.Object oriented modeling (OOM) has become an integral part of the design process in construction due to advances in computer software. Despite these advances there remains a tendency for Computer-Aided-Design (CAD) to be used as the medium to assist in the creation, modification, analysis and optimization of Electrical and Instrumentation (E&I) systems within heavy industrial engineering projects. In this paper, a retrospective OOM (i.e., Systems Information Model (SIM)), for the E&I systems of a utility facility, which was constructed for an Engineering Procurement and Construction (EPC) contractor for the purpose of undertaking a constructability assessment prior to the commencement of construction is presented and discussed. The CAD drawings and cable schedule produced by the EPC were provided to an E&I organization to undertake a constructability assessment; errors, omissions and information redundancy were identified and quantified. The SIM model was then used to examine a tender proposal from a construction subcontractor (CS) of the EPC; discrepancies were identified and it is suggested that differences arose due to the prevailing errors and omissions. The potential use of a SIM during construction as a quality assurance/control (QA/QC) is then examined, as it is suggested that it can be used to ensure the development of an ‘As-built’ model and provide a realistic representation of the constructed asset, which safeguards its integrity for operations and maintenance.